The Particular Reasons of the Impact of Covid-19 on Unemployment Level: The Case of European Union - Vusala GUBATOVA (Communications of International Proceedings, 2021)
The purpose of this article is to investigate the impact of Covid-19 on unemployment level in different EU countries and to determine the particular reasons of the impact of the pandemic on unemployment level. In the article, firstly the impact of Covid-19 on total unemployment level in EU member countries and its impact on unemployment level by sex and age have been revealed based on calculations of percentage changes of the relevant unemployment levels in 2020 in comparision to 2019. Then the factors that can cause the unemployment level to be increased during the pandemic have been determined in order to define the particular reasons of unemployment in European Union. Based on multiple regression analysis, it is justified that unemployment level is positively related with the number of active covid cases and the number of business closures, but negatively related with the number of products exported to other countries and the households’ major purchases which represent internal consumer demand. Moreover, the effect of using technologies and working from home on employment has been mentioned at the end of the article.
Keywords: Covid-19 pandemic; EU countries; labor market; unemployment level